Review of Siyasah Fiqh on Granting Legal Standing to Foreign Citizens in Judicial Review - Nanda Agwin Apriliansa; Abdul Kholiq Syafa'at (Rule of Law Studies Journal, 2026)
Background:The increasing mobility of foreign nationals (WNA) in the era of globalization has led to an increasingly intense interaction with the national legal system. In the context of a state based on the rule of law, every individual within the country's jurisdiction can be impacted by various laws and regulations. However, in the Indonesian legal system, the provisions of Article 51 paragraph (1) of the Constitutional Court Law explicitly limit the parties who can file a judicial review to only Indonesian citizens. This situation has given rise to debate regarding the legal standing of foreign nationals in the mechanism for testing laws at the Constitutional Court. Aims:This study aims to analyze the legal standing of foreign citizens in submitting judicial reviews to the Indonesian Constitutional Court and to review this practice through the perspective of fiqh siyasah, particularly the concepts of al-musta'min and al-'adl. Methods:This research employs a normative juridical approach using the statute approach, the conceptual approach, and the case approach. Data were obtained through a literature review of relevant laws and regulations, Constitutional Court decisions, books, and scientific journals. The data were then analyzed qualitatively to interpret legal norms and examine the practice of granting legal standing to foreign nationals from a fiqh siyasah perspective. Result:The research results show that, normatively, foreign citizens are not explicitly recognized as applicants in the judicial review mechanism under the Constitutional Court Law. However, in practice, there are dynamic interpretations in several Constitutional Court decisions that consider the legal interests of foreign parties. From a fiqh siyasah perspective, the concept of al-musta'min and the principle of al-'adl indicate that foreigners legally residing in a territory have the right to legal protection and access to justice. Conclusion:This study concludes that although the Indonesian legal system normatively limits legal standing to Indonesian citizens, a more inclusive approach can be considered to ensure the principle of universal justice and the protection of human rights. The integration of the fiqh siyasa perspective provides a normative foundation that reinforces the importance of access to justice for foreign citizens within the constitutional legal system